On the high resolution spectroscopy and intramolecular potential function of SO2; Journal of Molecular Spectroscopy; Vol. 257, iss. 2 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bekhtereva E. S. Elena Sergeevna; Alanko S.; Horneman V.-M.; Gromova O. V. Olga Vasilievna; Leroy K. A. Klod (Claude) Andre (2009, 2009)
Title screen